Effect of Extraction Time on the Quality of Durian Peel Pectin - Lenty Artha Siregar; Rona J Nainggolan; Mimi Nurminah (Universitas Sumatera Utara, 2014)
This research was aimed to know the effect of extraction time on the quality of durian peel pectin and to know how to extract pectin and to add economic value of durian peel waste. This research was conducted using a completely randomized design with one factor, namely the extraction time, 1 hour, 2 hours, 3 hours, 4 hours and 5 hours. The parameters analyzed were yield, moisture content, ash content, equivalent weigh, methoxyl content, galacturonic level and colour. Extraction time had highly significant effect on yield, moisture content, ash content, equivalent weight, methoxyl content, galacturonic level, and had no effect equivalent weight and colour. 5-hour extraction produced the best quality durian peel pectin. Keywords : durian peel, extraction time, pectin